Enforcement of spatial planning laws in controlling spatial use permits in Yogyakarta - Kuncorowati, Puji Wulandari; Handayani, I Gusti Ayu Ketut Rachmi; Subekti, Rahayu (Jurnal Civics: Media Kajian Kewarganegaraan, 2024)
Space is an area that includes land space, sea space and air space, including space within the earth as a unified territory, where humans and other creatures live, carry out activities and maintain their survival. Increasing population growth has an impact on the economic development of the people of an autonomous region who will undoubtedly utilize space that is considered strategic to support their economic activities. The complexity of development growth in Indonesia requires priority development programs and plans in various aspects or fields, but this development must not conflict with the fifth principle of Pancasila, namely social justice for all Indonesian. There is no consistency in implementing regulations, especially in enforcing laws related to spatial planning, which results in inappropriate development growth which impacts the surrounding environment, and green open space becoming increasingly narrow.